Analisis Sistem Pengendalian Intern Dinas Sosial Kabupaten Labuhan Batu Bara - Rizki Kartika Yani Lubis; Junita Putri Rajana Harahap (Pusat Riset dan Inovasi Nasional, 2024)
Management of social funds is an integral part of the government's efforts to maintain community welfare. These social funds are the main instrument in overcoming social inequality, protecting vulnerable individuals and families, and ensuring that their basic rights are fulfilled. The aim of this research is to analyze the Internal Control System of the Labuhan Batu Bara Regency Social Service. This research uses qualitative research methods. The research method used is in-depth interviews with research subjects, observation and documentation. Based on the research results, the social assistance internal control system in North Labuhan Batu Regency is designed to ensure that aid distribution is carried out effectively, on target and in accordance with applicable policies. This system includes several important components, starting with administrative controls that involve creating and implementing clear policies and procedures for the management and distribution of aid. Based on the research that has been conducted, it can be concluded that the internal control system for Social Assistance in North Labuhan Batu Regency is designed to ensure that the implementation of assistance is carried out effectively, accurately and in accordance with applicable policies.